About the peculiarities of cuticulaglifics of the hind leg of the Ceratophyllidae family fleas (Insecta, Siphonaptera) - E. V. Krasnikova (Юг России: экология, развитие)
The peculiarities of cuticulaglifics (“patterns” out of cuticular plates) of the hind leg of the fleas of the Ceratophyllidae family representatives, which are the distinctive features of many species, subfamilies and families are presented in this article.